2013
DOI: 10.1128/jb.00358-13
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-Hydroxybutyrate) Degradation in Ralstonia eutropha H16 Is Mediated Stereoselectively to (S)-3-Hydroxybutyryl Coenzyme A (CoA) via Crotonyl-CoA

Abstract: bDegradation of poly(3-hydroxybutyrate) (PHB) by the thiolytic activity of the PHB depolymerase PhaZ1 from Ralstonia eutropha H16 was analyzed in the presence of different phasins. An Escherichia coli strain was constructed that harbored the genes for PHB synthesis (phaCAB), the phasin PhaP1, and the PHB depolymerase PhaZ1. PHB was isolated in the native form (nPHB) from this recombinant E. coli strain, and the in vitro degradation of the polyester was examined. Degradation resulted in the formation of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 48 publications
1
47
0
1
Order By: Relevance
“…4). In summary, our data indicate that PHB granules of NB-gluconategrown R. eutropha cells have two other PHB depolymerases (A0671 and B1632) that could contribute to the PHB mobilization ability of R. eutropha, in addition to PhaZa1 (22,37,43,61). However, B1632 and A0671 do not have amino acid similarities to PhaZa1 or to other known intra-or extracellular PHB depolymerases and probably represent-together with Avin03910 -a novel type of intracellular PHB depolymerase with high molecular mass (80 to 90 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…4). In summary, our data indicate that PHB granules of NB-gluconategrown R. eutropha cells have two other PHB depolymerases (A0671 and B1632) that could contribute to the PHB mobilization ability of R. eutropha, in addition to PhaZa1 (22,37,43,61). However, B1632 and A0671 do not have amino acid similarities to PhaZa1 or to other known intra-or extracellular PHB depolymerases and probably represent-together with Avin03910 -a novel type of intracellular PHB depolymerase with high molecular mass (80 to 90 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular degradation of P(3HB) results in the liberation of 3-hydroxybutyric acid which is then oxidized by a dehydrogenase to acetoacetylCoA, which is finally converted into acetyl-CoA by β-ketothiolase (Eggers and Steinbüchel, 2013;Lemes et al, 2015). The breakdown products of PHA are naturally found in animals.…”
Section: Intracellular Degradationmentioning
confidence: 99%
“…Notably, the PHA degradation process is not simply along the reverse pathway of PHA synthesis. Crotonyl-CoA and (S)-3HB-CoA (one stereoisomer of 3HB-CoA) were recently found to be involved in nPHB degradation, which indicated that PHB degradation is separate from PHB synthesis and is connected to the ␤-oxidation cycle in Ralstonia eutropha (9).…”
mentioning
confidence: 99%
“…PhaZa1 degrades nPHB to 3HB-CoA in the presence of CoA (8,9), whereas PhaZb and PhaZc mainly hydrolyze 3HB oligomer to 3HB (12,13). PhaZd degrades artificial PHB (aPHB) and nPHB granules and releases mainly 3HB oligomer with only a small amount of 3HB monomer (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation